Simulation Research of Spray Lubrication and Optimization of Nozzle Position in a Complex Gearbox - Qian Xueling; Hu Yumei; Zhou Yuancong; Zhang Bo; Chen Guang; Shi Yanyan (Jixie chuandong)
The numerical simulation of spray lubrication and improvement of lubricant condition in a complex gearbox are researched. An experimental rig for spray lubrication of a pair of high-speed gears is set up and relevant experiments are carried out firstly. The experimental results are used to verify the correctness of numerical simulation method. Then numeric model of spray lubrication in a complex gearbox is established and simulation as well as analysis are conducted. The results show that overlong spray distance,angle of end face and jet flow on out of mesh side make against to lubrication. Then optimization of spray angle based on single-phase flow computational method is studied. Result show that,there is a weakest trace of air in the center plane of meshed gears. And if the axis of the nozzle lays on this trace,the meshed gears will have their best lubricant performance.